2010
DOI: 10.1307/mmj/1272376025
|View full text |Cite
|
Sign up to set email alerts
|

Topological aspects of Poset spaces

Abstract: We study two classes of spaces whose points are filters on partially ordered sets. Points in MF spaces are maximal filters, while points in UF spaces are unbounded filters. We give a thorough account of the topological properties of these spaces. We obtain a complete characterization of the class of countably based MF spaces: they are precisely the second-countable T 1 spaces with the strong Choquet property. We apply this characterization to domain theory to characterize the class of second-countable spaces w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Stephan [23] have shown that the spaces that are homeomorphic to the maximal elements of some ω-continuous domain are precisely the countably based strong Choquet spaces that satisfy the T 1 -separation axiom (K. Martin had previously shown that the maximal elements are strong Choquet).…”
Section: ⊓ ⊔mentioning
confidence: 99%
“…Stephan [23] have shown that the spaces that are homeomorphic to the maximal elements of some ω-continuous domain are precisely the countably based strong Choquet spaces that satisfy the T 1 -separation axiom (K. Martin had previously shown that the maximal elements are strong Choquet).…”
Section: ⊓ ⊔mentioning
confidence: 99%
“…(3) The maximal antichain space A co max is not quasi-Polish. For (1), [43,Theorem 6.1] by Mummert and Stephan implies that the Gandy-Harrington space can be represented as the maximal elements of an omega-algebraic domain. Therefore, the Gandy-Harrington space embeds as a (necessarily strict) co-analytic subset of a quasi-Polish space.…”
Section: Example 331 (Mccarthymentioning
confidence: 99%
“…(f) Domain theory and associated topologies are studied in RM ( [64,78]), and nets take central stage in domain theory in [44,45,47]. (g) Nets are used in topological dynamics ( [41]), which is studied in the proof mining program ( [43,60]).…”
Section: Aim and Motivationmentioning
confidence: 99%